Analysis Scientific Knowledge of The Process Making Jenang Kudus and Its Potential for Empowering Logical Thinking Skills - Ainuzzahroh, Naila Zulfa; Suciati*, Suciati; Utami, Budi; Silvita, Silvita; Prasetyo, Opik; Rachman, Hening Triandika (Universitas Syiah Kuala, 2024)
The low knowledge of students' local wisdom, especially jenang kudus, has an impact on Indonesia's identity in the future. In addition, Indonesian students have low logical thinking skills, this also affects the fading of local wisdom in Indonesia, students have difficulty filtering foreign cultures carried by globalization. This study aims to: (1) analyze the scientific knowledge contained in the process of making jenang Kudus; (2) analyze the potential of scientific knowledge contained in the process of making jenang Kudus to empower junior high school students' logical thinking skills; (3) analyze the relationship of scientific knowledge contained in the process of making jenang Kudus to the material in science learning. This research is a descriptive qualitative research with an ernographic approach. The data sources include informants and articles. The sampling technique was done with snowball sampling technique. Data collection was collection using interview, observation, documentation and journal analysis. The data validity test technique was carried out using triangulation techniques. Data analysis techniques using interactive analysis techniques. The results of this study show that the process of making Jenang Kudus contains scientific knowledge of science from three aspects including biology, chemistry and physical. Scientific knowledge in the process of making jenang Kudus has the potential to empower logical thinking skills which include 5 indicators including ordering, comparing, contrasting, evaluating, selecting. Scientific knowledge in the process of making jenang Kudus is related to junior high school science materials including temperature and heat, mixtures, physical and chemical changes, additives, and food substances.